The effect of genetic variants of SLC22A18 on proliferation, migration, and invasion of colon cancer cells - Hyo Sook Song; Seung Yeon Ha; Jin-Young Kim; Minsuk Kim; Ji Ha Choi (Scientific Reports, 2024)
Abstract Solute carrier family (SLC) transporters are expressed in the digestive system and play important roles in maintaining physiological functions in the body. In addition, SLC transporters act as oncoproteins or tumor-suppressor proteins during the development, progression, and metastasis of various digestive system cancers. SLC22A18, a member of the SLC22 gene family, is an orphan transporter with an unknown endogenous substrate. Previous study revealed that SLC22A18 is downregulated in colorectal cancer tissues and that it acts as a suppressor in colorectal cancer, although the effects of SLC22A18 variants on colon cancer cell proliferation, migration, and invasion are unknown. Therefore, in this study, we identified SLC22A18 variants found in multiple populations by searching public databases and determined the in vitro effects of these missense variations on transporter expression and cancer progression. Our results indicated that three missense SLC22A18 variants—p.Ala6Thr, p.Arg12Gln, and p.Arg86His—had significantly lower cell expression than the wild type, possibly owing to intracellular degradation. Furthermore, these three variants caused significantly higher proliferation, migration, and invasion of colon cancer cells than the wild type. Our findings suggest that missense variants of SLC22A18 can potentially serve as biomarkers or prognostic tools that enable clinicians to predict colorectal cancer progression.